CLINICAL STUDIES TO EVALUATE PEROXIDATIVE STRESS AND ANTIOXIDANT COMPLEMENT IN LIVER CANCER IN INDIAN AND HUNGARIAN SUBJECTS - KUMAR, SAMAR RAJENDRA; SUMAN, JAIN; SONAL, SOGANI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Liver cancer is the leading cause of death due to malignancies all over the world. Free radical-induced oxidative stress extent can be provoked by antioxidant mechanisms decreased efficiency. The present study was carried out to investigate the extent of oxidative stress and the levels of antioxidants in the circulation of patients with liver cancer. Methods: Plasma thiobarbituric acid reactive substances (TBARS) and level of some antioxidant enzymes as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and GSH be determined in the circulations of 100 Indian and Hungarian patients with liver cancer and an equal number of age-matched normal subjects. Results: Significantly increased concentrations of TBARS plasma levels and significantly lowered levels of SOD, CAT, GSH, and GSH-Px were observed in patients with liver cancer which may have occurred due to increased use to scavenge lipids peroxides as well as their sequestration by tumor cells. Increased lipid peroxidation in liver was seen which may be due to excessive oxidative stress. Comparison between Indians and Hungarians subjects revealed 200% increased malondialdehyde levels in Hungarian male patients as compared to Indian male patients. SOD was found to decrease in Indian subjects whereas CAT (20%) higher, GSH (25–35%) less decrease GSH-Px (5%) more decrease in Hungarians patients compared to Indian patients.